Assessment of the learning facilities in the UP Visayas Iloilo City Campus through the satisfaction and importance level of students using IT, and the introduction of learning commons - Adanza, Detlef; Deloria, Camille Faye.; Garol, Kenneth Jules; Mina, Jim Louie (2018.)
In recent years, there has been a substantial development in education around the world especially the rise fo the Learning commons. This venue has been accompanied by a debate on the quality of its facilities as well as its role that they may have within the education system. On the other hand, most of the schools are still using the traditional learning facilities such as the libraries and study halls. In order to address this problem, this study aims to understand and measure how tertiary school students perceive their learning facilities and identify the key factors affecting these perceptions. The objective taken in this academic paper is to determine whether the learning facilities that are currently existing in the Universiry of the Philippines Visayas - Iloilo City campus are perceived by the students as important and also to determine whether thay are satisfied or not in using them. The collection of data was through a survey conducted to 82 students in the College of Management in the University of the Philippines Visayas - Iloilo City Campu. The results indicsted that the students perceived that most of the currently existing learning facilities are important and that they are satisfied in using them. However, the findings also indicate that there is a significant amount of the respondents that say that they want to establish a Learning Commons within the University and that by doing so will improve their academic performance
Research Paper (BA 199 - Business Research) -- [Iloilo City : University of the Philippines Visayas-College of Management], May 2018.